PENERAPAN NETWORK ANALISIS DALAM PENENTUAN RUTE TERCEPAT MENUJU SHELTER UNTUK MITIGASI BENCANA TSUNAMI DI KOTA PAINAN - Geni Handani Putra; Febriandi Febriandi (DEPARTEMEN GEOGRAFI FIS UNP, 2021)
The main problem in this research is how the fastest route to the shelter in Painan City using Network Analysis as a reference for the results of the fastest route to the shelter. The purpose of this study was to determine (1) the distribution of tsunami prone zones in Painan City, (2) the availability of shelters in Painan City, (3) The fastest route to the shelter in tsunami disaster mitigation in Painan City. This type of research is a quantitative research with the steps of collecting data related to research from agencies related to this research. The data needed in this research such as disaster data, shelter availability data, and shelter capacity data are obtained at BPBD (Regional Disaster Management Agency) Painan City, while supporting data such as road data, slope data, population data are obtained from the PUPR Agency (Public Works and Spatial Planning) and BPS (Central Statistics Agency) of Painan City. The steps of this research are: (1) type of research, (2) population and sample, (3) location and time, (4) tools and materials, (5) data collection techniques, (6) data analysis techniques. The results of this study indicate that First Painan City is in an area with a high level of tsunami hazard. This is due to the geographical location of Painan City which is close to the coast, and Nagari which is at a high level of vulnerability are Nagari Painan Selatan, while Nagari Painan Utara and Nagari Painan Timur. being at a sedentary and low tsunami hazard level, both Painan City have eight shelters available. It consists of three natural shelters and five artificial shelters with a capacity of 29,000 people. Meanwhile, based on data from BPS IV Jurai in 2020, the population of Painan City is 16589 people, so it can be concluded that the availability of shelters and shelter capacity in Painan City is sufficient to accommodate the people of Painan City. The third fastest route in tsunami disaster mitigation in Painan City, there are several shelters that are dominant to be used as shelters. This can be seen based on the results of the Network Analysis that get the closest shelter by the community, namely the Regent's Office, SMPN 1 Painan and the Baiturahman Mosque. Meanwhile, other shelters can be used as alternative shelters if the dominant shelter is full.